Genetic Engineering Technique in Virus-Like Particle Vaccine Construction - Debie Rizqoh (Universitas Muhammadiyah Semarang, 2021)
Vaccine becomes a very effective strategy to deal with various infectious diseases even to the point of eradication as in the smalpox virus. At present many conventional vaccines such as inactivated and live-attenuated vaccines. However, these vaccine methods have side effects on the population. Viral-like particle (VLP) is an alternative vaccine based on recombinant DNA technology that is safe with the same immunogenicity as conventional viruses. This vaccine has been shown to induce humoral immune responses mediated by antibodies and cellular immune responses mediated by cytotoxic T cells. With these advantages, currently various types of vaccines have only been developed on a VLP basis. VLP can be produced from a variety of recombinant gene expression systems including bacterial cell expression systems, yeast cells, insect cells, mammalian cells, plant cells, and cell-free systems.